1978
DOI: 10.1093/infdis/137.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Gonorrhea: An Analysis of Importance and Risk Factors

Abstract: This study was designed to assess the epidemiological importance of repeated infections due to Neisseria gonorrhoeae and to analyze variables potentially associated with repeated gonorrhea. The retrospective analysis was of 7,347 patients seen during one year, and the prospective study was of a stratified randomly selected sample of 429 patients. The 492 retrospectively identified repeaters constituted 0.06% of the county population and 6.7% of the clinic population. The 492 repeaters had 21.6% of the cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…It is clear that individuals with repeated infections contribute disproportionately to the overall STD clinic burden [3,9,22,[29][30][31][32][33]. The ability to identify early those individuals who are likely to become reinfected would thus provide a potential avenue to channel clinics' limited prevention and screening resources more effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that individuals with repeated infections contribute disproportionately to the overall STD clinic burden [3,9,22,[29][30][31][32][33]. The ability to identify early those individuals who are likely to become reinfected would thus provide a potential avenue to channel clinics' limited prevention and screening resources more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to identify early those individuals who are likely to become reinfected would thus provide a potential avenue to channel clinics' limited prevention and screening resources more effectively. Previous studies of gonococcal reinfection have focused predominantly on demographic characteristics (young age, male sex, lower socioeconomic status, minority race, single marital status, and unemployment) [9,30,31,34,35] and geographic characteristics [3,22] for defining this core. Lundin et al found in 1977 that social and psychological characteristics of repeaters were distinct from those of nonrepeaters [36].…”
Section: Discussionmentioning
confidence: 99%
“…Because the focus of the analysis was repeat infection rather than treatment failure, antibiotic efficacy studies, which generally have short-term follow-up, were not included in our analysis. Twenty-three studies were excluded because reinfection rates were not stratified by sex [11][12][13][14][15][16][17][18][19][20][21] or specific etiology (chlamydia or gonorrhea), 13,14,[21][22][23][24] the publication was a nonpeer-reviewed letter, 25 data were duplicative of already published material, 26 -28 reinfection rates could not be calculated using the data provided, 29 -32 or initial infection was not laboratory-confirmed. 33 Specific study design, proportion of females retested, diagnostic test type used, length of follow-up, geographic region, and population demographics were not considered in the inclusion and exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…6,[22][23][24][25][26][27] Gonorrhea reinfections after treatment have consistently found to be associated with male gender, 23,25 black race, 23,[25][26][27][28][29] younger age, 23,25,26 low socioeconomic status, [25][26][27][28] and increased number of sexual partners. 25,26,29 In Baltimore, we have shown that those with reinfections were more likely to live closer to other repeaters. 6 However, most studies of reinfection are limited to retrospective cohorts defined through clinic or health department data, where most infections detected are through testing those with clinical symptoms.…”
mentioning
confidence: 99%